(untitled) (Indian Journal of Arid Horticulture, 2025)
Genetic variability and character association were studied for yield and its component characters in 20 genotypes of pea (Pisum sativum L.) during rabi, 2009-10. Analysis of variance revealed significant difference for all the characters indicating the presence of good amount of variability in the genotypes studied. The estimates of GCV, heritability and genetic gain were higher for plant height, whereas, high heritability with moderate GCV and genetic gain were observed for days to first flowering, days to 50% flowering, days to first fruit setting, days to first pod picking and number of pickings, indicating good scope for selection. Association studies revealed that green pod yield per plant was positively and significantly associated with pod length, pod weight and number of grains per pod. The result suggested that these traits could be considered as major yield contributing traits in garden pea.